2013
DOI: 10.1051/alr/2013055
|View full text |Cite
|
Sign up to set email alerts
|

Family effect on cultured pearl quality in black-lipped pearl oysterPinctada margaritiferaand insights for genetic improvement

Abstract: -Individual Pinctada margaritifera molluscs were collected from the Takapoto atoll (Tuamotu Archipelago, French Polynesia) and used to produce ten first generation full-sib families in a hatchery system, following artificial breeding protocols. After three years of culture, these progenies were transferred to Rangiroa atoll (Tuamotu Archipelago, French Polynesia) and tested for their potential as graft donors. A large-scale grafting experiment of 1500 grafts was conducted, in which a single professional grafte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
101
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(108 citation statements)
references
References 20 publications
6
101
1
Order By: Relevance
“…For example, Snow et al [37] hypothesized that pearls with a smooth surface and brilliant lustre are produced when consistent and regular crystal formation occurs, which is not compatible with a high nacre deposition rate. Ky et al [9] showed a strong family effect on pearl weight, but a significant effect of pearl colour was also detected, as well as a significant family * colour interaction. This indicates that potential relationships between weight and colour may vary among families.…”
Section: Family Effect On Shell Growth Performancementioning
confidence: 95%
See 2 more Smart Citations
“…For example, Snow et al [37] hypothesized that pearls with a smooth surface and brilliant lustre are produced when consistent and regular crystal formation occurs, which is not compatible with a high nacre deposition rate. Ky et al [9] showed a strong family effect on pearl weight, but a significant effect of pearl colour was also detected, as well as a significant family * colour interaction. This indicates that potential relationships between weight and colour may vary among families.…”
Section: Family Effect On Shell Growth Performancementioning
confidence: 95%
“…Some keshi (small irregular shaped nacreous but non-nucleated pearls that form during the culture period after nuclei have been rejected) were also harvested, but not graded. Cultured pearls were then cleaned by ultrasonication in soapy water (hand washing) with a LEO 801 laboratory cleaner (2 L capacity, 80 W, 46 kHz) according to Ky et al [9]. Each pearl was mm) depends on pearl farming site as, in French Polynesia, the annual growth rate in shell size varies from 19.7 mm to 31.8 mm year -1 [23].…”
Section: Cultured Pearl Weight Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological mechanisms influencing rates of RS, CL, RT and OT (without circles) cultured pearl shapes are complex and only a few studies have focussed on the determining factors of these shapes in P. margaritifera. Using oysters produced in the hatchery system, Ky et al (2013) revealed that the presence of circled pearls was not influenced by donor family. In contrast, selection of donor oysters from the wild (Tayale et al, 2012) or produced in the hatchery (Ky et al, 2013) would be effective in increasing the proportion of round and semi-round pearls and decreasing the number of rejects.…”
Section: Introductionmentioning
confidence: 99%
“…Using oysters produced in the hatchery system, Ky et al (2013) revealed that the presence of circled pearls was not influenced by donor family. In contrast, selection of donor oysters from the wild (Tayale et al, 2012) or produced in the hatchery (Ky et al, 2013) would be effective in increasing the proportion of round and semi-round pearls and decreasing the number of rejects. A recent study revealed a significant phenotypic correlation between cultured pearl quality (grade) and shape in P. margaritifera (Ky et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%